Chapter Exploring Globalization with Cosmopolitics - Scannapieco, Monica (Proceedings e report, 2023)
Cosmopolitics, an open-source dashboard designed by an Istat team to perform exploratory data analysis using Eurostat statistical open data on international trade, offers several tools for investigating globalization phenomena such as the dynamics of global value chains (GVC). The advantage of this widely spread economic organization is well known: companies obtain economic advantages by direct foreign investments or by production outsourcing, i.e. relocating some production phases to countries where high specialization or an advantageous labor market create greater opportunities. However, by its very nature, the GVC is highly sensitive to shock transmissions and supply chain disruptions associated with geopolitical events or epidemiological crises. The dashboard will be released as Istat experimental statistical product and available online. Through a Social Network Graph Analysis approach, it will offer students, researchers and policy makers the opportunity to explore the dynamics of global trade for specific products traded by different modes of transport. The tool allows users not only retracing recent critical phases affecting global trade, but also interactively simulating bilateral trade flows interruptions or closures of specific logistic poles or transport routes. This gives the opportunity to outline possible scenarios in which the GVC trade relationships reshape under shock transmissions, such as conflicts, changes in bilateral relationships between countries, logistics or transport new arrangements, reallocation of foreign investments, etc. By computing standard Social Network indicators (such as graph density, indegree, outdegree, and closeness centrality), the tool provides many quantitative measures associated with the specific global trade structures displayed. This paper will illustrate the methodology implemented in the dashboard and will provide examples on how to explore GVC scenarios by Cosmopolitics.